The switch [compact disc, unabridged] - O'Leary, Beth (Macmillan Audio, 2020)
When overachiever Leena Cotton is ordered to take a two-month sabbatical after blowing a big presentation at work, she escapes to her grandmother Eileen's house for some long-overdue rest. Eileen is newly single and about to turn eighty. She'd like a second chance at love, but her tiny Yorkshire village doesn't offer many eligible gentlemen. So they decide to try a two-month swap. Eileen will live in London and look for love. Meanwhile Leena will look after everything in rural Yorkshire. But stepping into one another's shoes proves more difficult than either of them expected.